Conditions to Ensure Competitive Hybridization in Two-Color Microarray: A Theoretical and Experimental Analysis. (June 2002) - Wang, Youmin; Wang, Xujing; Guo, Sun-Wei; Ghosh, Soumitra
We derived a theoretical model that explains certain biases observed in the twocolor microarray hybridization experiments reported in the literature. We show that true competition is achieved only when the hybridization kinetics of the two differentially labeled probes are the same. If the hybridization kinetics of the two differentially labeled probes is different, which can occur when the labeling and hybridization conditions for the two probes are dissimilar, then differential expression observed becomes a function of the amount of the target (i.e., DNA spotted on the slide). We use this model to validate the microarray methodology by determining the differential expression of four select Arabidopsis genes and two human genes ( β -actin and GAPDH) as a function of the amount of target arrayed. We show through both modeling and experiments that the rate constants for Cy5- and Cy3-labeled probes are the same under our experimental conditions. Therefore, the target concentrations need not greatly exceed the probe concentration. It is obvious from the data presented that a simple treatment of an individual hybridization rate calculation does not fully describe what is occuring in today's complex, multispecies experiments. The method of validation is easily implemented to ensure data reliability by two-color microarray.